2009
DOI: 10.1038/nn.2361
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic basis of partial agonism at NMDA receptors

Abstract: Activation of ligand-gated channels is initiated by the binding of small molecules at extracellular sites and culminates with the opening of a membrane-embedded pore. To investigate how perturbations at ligand-binding domains influence the gating reaction, we examined current traces recorded from individual NMDA receptors in the presence of several subunit-specific partial agonists. Here we show that low-efficacy agonists acting at either the GluN1 or the GluN2A subunit had very similar effects on the receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(141 citation statements)
references
References 43 publications
18
123
0
Order By: Relevance
“…Conceptual Models of GluN1/GluN2B Receptor Activation. In recent years, a number of conceptual models for NMDA receptor gating have been proposed (Banke and Traynelis, 2003;Popescu and Auerbach, 2003;Auerbach and Zhou, 2005;Erreger et al, 2005;Schorge et al, 2005;Dravid et al, 2008;Kussius and Popescu, 2009). Together with structural information, these conceptual models may allow determination of steps involved in receptor activation that define macroscopic currents and synaptic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Conceptual Models of GluN1/GluN2B Receptor Activation. In recent years, a number of conceptual models for NMDA receptor gating have been proposed (Banke and Traynelis, 2003;Popescu and Auerbach, 2003;Auerbach and Zhou, 2005;Erreger et al, 2005;Schorge et al, 2005;Dravid et al, 2008;Kussius and Popescu, 2009). Together with structural information, these conceptual models may allow determination of steps involved in receptor activation that define macroscopic currents and synaptic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Future work may reveal why HCY decreases peak amplitude of GluN2B NMDAR responses while continuing to reduce desensitization. It may be that HCY resembles partial GLY site agonists such as L-alanine, which reduce GLYdependent NMDAR desensitization but decrease receptor opening probability relative to full agonists Kussius and Popescu 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors have robust single-channel activity, with a single conductance level (1). Kinetic analyses of single-channel currents have revealed that during stationary gating, the channelclosed state contains three components (C 3 , C 2 , and C 1 ) outside desensitization and the channel-open state contains two or more components, which are often collectively denoted as O (9)(10)(11)(12). The molecular nature of these kinetic components remains unknown, although mutational effects on the populations and transition rates of these components have provided some hints (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%